Integrating Drug-Related Problems Identification and INA-CBGs Cost Gap Analysis in Hemorrhagic Stroke Patients with Hypertension: A PCNE-Based Systematic Review - Deddy Setyagus Ariawan; Dhanang Prawira Nugraha; Fithria Dyah Ayu; Vitarani Dwi Ananda Ningrum; Julaeha Julaeha (GLOBAL HEALTH SCIENCE GROUP, 2025)
Hemorrhagic stroke with comorbid hypertension is a complex clinical condition with a high economic burden. In the National Health Insurance (JKN) financing system, INA-CBG package rates often do not reflect the actual costs incurred by hospitals. One potential factor contributing to this cost gap is Drug-Related Problems (DRPs), which include incorrect dosing, drug interactions, and inappropriate therapy.Objective to assess the impact of DRPs on the cost gap between INA-CBG tariffs and actual costs of hemorrhagic stroke care with hypertension, as well as to evaluate the effectiveness of the PCNE method in identifying DRPs. Following PRISMA guidelines, a literature search was conducted on PubMed, ScienceDirect, ProQuest, and Google Scholar (2020–2025) using keywords related to hemorrhagic stroke, hypertension, cost-effectiveness, INA-CBGs, and PCNE. Primary studies analyzing DRPs and/or comparing actual costs with INA-CBGs tariffs in hemorrhagic stroke patients were included. The data were synthesized narratively, focusing on types of DRPs, application of PCNE, and cost gaps. Of 195 articles, 11 were included in the synthesis, with 3 highly relevant. DRPs (eg, inappropriate drug selection) were detected in over 60% of cases using PCNE, leading to increased costs. The gap between actual costs and INA-CBGs tariffs reached up to IDR 8 million. DRPs are significant determinants of cost inefficiency in the care of hemorrhagic stroke patients with hypertension. Systematic implementation of the PCNE method integrated with pharmacoeconomic evaluation is recommended to support the sustainability of JKN. This study suggests tariff adjustments for INA-CBGs and an expanded role for pharmacists.